2013
DOI: 10.1111/wej.12064
|View full text |Cite
|
Sign up to set email alerts
|

The impact of wastewater irrigation on the chemical quality of groundwater

Abstract: The purpose of this investigation was to assess the groundwater impact of irrigation with industrial wastewater (baker's yeast wastewater, BYW) and to determine if agricultural reuse can be considered as an efficient wastewater treatment method. The impact of the irrigation and the status of the groundwater quality were determined using chemical parameters that are typical contaminants of BYW and characterise the content of total suspended solids (TSSs), organic matter (biochemical and chemical oxygen demands)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This leads to a decrease in the use of fertilizers and the treatment of the groundwater aquifer in the soil. This results in a lack of direct discharge, and supply of nutrients to water bodies [ 20 ]. Abd-Elaty et al [ 21 ] carried out geotechnical and numerical study for applied solutions to reduce soil and groundwater contamination by fertilizers in arid and semi-arid regions in the Eastern Nile Delta, Egypt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a decrease in the use of fertilizers and the treatment of the groundwater aquifer in the soil. This results in a lack of direct discharge, and supply of nutrients to water bodies [ 20 ]. Abd-Elaty et al [ 21 ] carried out geotechnical and numerical study for applied solutions to reduce soil and groundwater contamination by fertilizers in arid and semi-arid regions in the Eastern Nile Delta, Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…As for the economic features, the following were used: reduced treatment costs for wastewater, reduced fertilizer costs, and reduced costs of freshwater; as for the negative aspects, they are formed in the damage to human health as well as environmental damage, as it requires a special distribution system for wastewater in order to be stored in the seasons in which it is not used [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For our integrated approach, we need to identify how humans and the environment are exposed to contaminants, in this case focused on contaminants introduced by irrigation water. Contaminants can threaten the soil quality [30][31][32][33][34], crop quality [35][36][37], groundwater quality [20,38,39], surface water quality [40], and air quality [28,41]. The most important environmental compartments and contaminant pathways are summarized in Figure 1.…”
Section: Contaminant Balancementioning
confidence: 99%
“…Additionally, wastewater is applied directly without treatment in some regions. Commonly found contaminants in marginal water include heavy metals [12][13][14], alkali and earth alkali salts [15][16][17], nutrients [18][19][20], organic chemicals [21][22][23], and pathogens [7]. The presence of these contaminants makes it unclear whether long-term irrigation with marginal water is sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, reuse of some of the wastewaters should be considered in the baker's yeast industry. Paruch () reported that baker's yeast wastewater might be used for agricultural irrigation with limited negative effects on groundwater.…”
Section: Challenges For the 21st Century: Water Consumption And Pollumentioning
confidence: 99%